Capital estrangeiro nos setores de energia e de minerais estratégicos da economia Brasileira - Hugo C. Iasco-Pereira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This article documents the presence of foreign firms in the sectors of energy and strategic minerals of the Brazilian economy. For this purpose, it was employed the information provided by the Brazilian Federal Revenue Office on it. The results indicated little importance for foreign companies. Despite the sectoral heterogeneity, the study stresses the significant presence of domestic firms, or, to a lesser extent, of domestic firms with foreign partners in both sectors. The study also analyzed the nationality of these foreign firms. It was noted strong presence of companies from the USA, Spain, Italy, Australia, Netherlands, United Kingdom, Germany, Canada, and Japan. Lastly, it was calculated an index to quantify the existence of foreign direct investment featured as greenfield or brownfield. The output indicates a certain sectoral heterogeneity, but with more importance of greenfield projects in relation to brownfield ones. Plus, it was found no evidence that foreign capital promotes exports of strategic minerals.
Keywords: F21; F18; F23; 330; foreign capital; mining; energy; Brazilian economy